(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract One of the healthworker who are competent in providing antenatal cara is a midwife. Association of indonesian midwive launching Bidan Delima Program to make midwife more professional. This research aim to obtain information about antenatal care by bidan delima in Pekanbaru. This research was qualitative research with phenomenalogical approach. The informan are Facilititator of bidan delima, woman who perform antenatal care to bidan delima, also bidan delima who selected by purposive sampling. Data collected with deep interview and checking documentation which is conducted by bidan delima. Data were analysis by source and technic triangulation. The result show there is a midwife who proovide TT imunization without rate imunization status. Bidan delima commonly did not have kit or tool to examine blood gr Hepatitis Boup, HIV, Sifilis dan. We expected bidan delima service unit organize training/ workshoop to upgrade bidan delima knowledge about antenatal care